Susceptibility of Malaysian rice varieties to Fusarium fujikuroi and in vitro activity of Trichoderma harzianum as biocontrol agent - Wan Abd Halim, Wan Nur Ain; Abd Razak, Azmi; Ali, Jambari; Mohd Zainudin, Nur Ain Izzati (Malaysian Society for Microbiology, 2015)
Aims: Bakanae disease on rice has been widely distributed in all countries where rice is grown commercially, especially in Asian countries including Malaysia. As an alternative measure in controlling Fusarium fujikuroi, two approaches have to be adapted i.e. by using resistant varieties and biocontrol agents as reported in the present study. Methodology and results: A total of 31 Malaysian rice varieties were used in screening and results showed that variety MR211 was the most susceptible and MR220 was slightly susceptible. Out of 60 isolates of Trichoderma harzianum isolated from soils in Malaysia and tested against the pathogen under in vitro condition, 13 isolates showed high percentage of inhibition (PIRG > 60%). All isolates of T. harzianum showed that the PIRGs were significantly different at p≤0.05 with those of control plates. Conclusion, significance and impact of study: Biocontrol agent and resistant variety are better alternative for controlling plant diseases. We found a variety MR220 was slightly susceptible, but none of tested varieties is resistant towards pathogen of bakanae disease. T. harzianum has the ability to inhibit the growth of F. fujikuroi (T3068P) under in vitro condition. The findings of the Malaysian susceptible/resistant variety and potential T. harzianum isolate as a biocontrol agent of bakanae are important for future tests in the plant house and field trials.